(3Cef GdeYdheGJ GdEdjcJQhfjI (B/s - (3eMeO GdLfHjgj, efjQs; (3GdLfHjgj, eeOhM eMeO s ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2005)
(3JGQjN GdCehQ, GdGYJQGa HGdQSGFd, GdajQhSGJ, GdOjOGf, hSGFd GdCeQjcjI GdCcGOjejI GSJNOGeG, GdJYGhf GdOhdj aj eLGd MeGjI GdNUhUjI GdeYdheGJjI, bGfhf Jbfjf GdeYdheGJ, bGfhf GdceHjhJQ, GdJTQjYGJ GdeGdjI hGdeUQajI ajeG jJUd HGdeGd GdGdcJQhfj hJbfjGJ GdNOeGJ GdeUQajI, GdJTQjYGJ MeGjI GdNUhUjI GdeYdheGJjI aj cGaI Ohd GdYGde, cjajI GdJNdU ef edaGJ GdGNJQGb, GdcYcGJ, GdVhGHW GdQbGHjI hYhGed GdCeGf ddYedjGJ GdeUQajI(B.s
(3GdeQGLY U(B.229s
Keywords: (3GdGdcJQhfjGJs; (3GdMGShH(B- (3GdbhGfjf hGdCfXeIs; (3GdbQUfIs; (3GdeYdheGJjIs; (3Cef GdeYdheGJ(B- (3bhGfjf hCfXeIs; (3LQGFe GdMGShHs